2008
DOI: 10.1515/cclm.2008.188
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular biomarkers: increasing impact of laboratory medicine in cardiology practice

Abstract: The practice of cardiology is in continual evolution, in parallel with the progress achieved by medical research in understanding the pathophysiology of cardiovascular disease and in developing new therapeutic procedures. Consequently, manufacturers of cardiac biomarkers are pressed with new demands to improve the performance of the existing and the development of novel ones. Several highly sensitive and/or specific assays for myocardial ischemic damage and myocardial function detection have already become com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 156 publications
1
51
0
2
Order By: Relevance
“…Moreover, some gene polymorphisms of specific natriuretic peptide receptors have associated with some cardiovascular diseases, including systemic arterial hypertension (72,74,96,106), cardiomyopathy (103), and stroke (75). However, the true clinical impact of these studies is still debated, considering that the most frequent cardiovascular diseases are polygenic disorders (99). Finally, at the postreceptor level, an increased activity of the cGMP phosphodiesterase (PDE) V, which metabolizes cGMP, may contribute to increase the resistance to the natriuretic peptide action.…”
Section: Resistance To the Biological Effects Of Cnhsmentioning
confidence: 99%
“…Moreover, some gene polymorphisms of specific natriuretic peptide receptors have associated with some cardiovascular diseases, including systemic arterial hypertension (72,74,96,106), cardiomyopathy (103), and stroke (75). However, the true clinical impact of these studies is still debated, considering that the most frequent cardiovascular diseases are polygenic disorders (99). Finally, at the postreceptor level, an increased activity of the cGMP phosphodiesterase (PDE) V, which metabolizes cGMP, may contribute to increase the resistance to the natriuretic peptide action.…”
Section: Resistance To the Biological Effects Of Cnhsmentioning
confidence: 99%
“…The multi-marker concept was put forward recently in diagnosing AMI, predicting disease risk and evaluating patient outcomes [21,22] . Mion et al used an automated protein biochip microarray system, which allowed a simultaneous determination of six biomarkers, and found that H-FABP+cTnI combination presented the highest sensitivity (83.3%) and specificity (92.2%), and favored it as the most effective "two marker strategy" of the five combinations determined in the study [23] .…”
Section: Discussionmentioning
confidence: 99%
“…By contrast to the remarkable progress of biomarkers in cancer and cardiovascular disease [17][18][19][20], there are very few validated biomarkers for the assessment of SSc disease activity and for clinical subset disease classification, and their utility has not been extensively tested or validated in clinical trials [21]. Most importantly, there is an important need to develop, test and validate accurate and objective measures of tissue fibrosis and vasculopathy in SSc and markers that may reflect a therapeutic response of the disease process for use in clinical trials.…”
Section: Biomarkers In Sscmentioning
confidence: 99%